Inhibition of Neovascularization and Inflammation in a Mouse Model of Corneal Alkali Burns Using Cationic Liposomal Tacrolimus - Lin, Xueqi; Yu, Xuewen; Chen, Xiang; Sheng, Siting; Wang, Jingwen; Wang, Ben; Xu, Wen (Frontiers in Bioengineering and Biotechnology, 2021)
Eye drops account for more than 90% of commercialized ophthalmic drugs. However, eye drops have certain shortcomings, such as short precorneal retention time and weak corneal penetration. The requirement of frequent instillation of eye drops also causes poor patient compliance, which may lead to further aggravation of the disease. We aimed to develop a cationic liposome formulation to increase the bioavailability of the therapeutic agent and solve the aforementioned problems. In the present study, we prepared cationic liposomal tacrolimus (FK506) with a surface potential of approximately +30 mV, which could bind to the negatively charged mucin layer of the ocular surface. Our results showed that the content of FK506 in the cornea was increased by 93.77, 120.30, 14.24, and 20.36 times at 5, 30, 60, and 90 minutes, respectively, in the FK506 liposome group (0.2 mg/mL) compared with the free drug group (0.2 mg/mL). Moreover, FITC-labeled FK506 liposomes significantly prolonged the ocular surface retention time to 50 minutes after a single dose. In addition, the results of the Cell Counting Kit-8 assay, live and dead cell assay, sodium fluorescein staining, and hematoxylin and eosin staining all indicated that FK506 liposomes had good biological compatibility in both human corneal epithelial cells and mouse eyeballs. Compared with the free drug at the same concentration, FK506 liposomes effectively inhibited vascular endothelial growth factor-induced green fluorescent protein-transduced human umbilical vein endothelial cell migration and tube formation in vitro, even when the drug concentration was as low as 5 μg/mL. In a mouse corneal neovascularization model induced by alkali burns, FK506 liposomes (0.2 mg/mL) enhanced corneal epithelial recovery, inhibited corneal neovascularization, and reduced corneal inflammation, and its therapeutic effect was better than those of the commercial FK506 eye drops (1 mg/mL) and the free drug (0.2 mg/mL). Collectively, these results indicate that cationic FK506 liposomes could increase the efficacy of FK506 in the corneal neovascularization model. Therefore, cationic FK506 liposomes can be considered as a promising ocular drug delivery system.